Interstitial Lung Disease in Rheumatoid Arthritis: A Practical Review - Laria, Antonella; Lurati, Alfredo Maria; Zizzo, Gaetano; Zaccara, Eleonora; Mazzocchi, Daniela; Re, Katia Angela; Marrazza, Mariagrazia; Faggioli, Paola; Mazzone, Antonino (Frontiers in Medicine, 2022)
Rheumatoid arthritis (RA) is a systemic inflammatory disease which primarily causes symmetric polyarthritis. An extrarticolar involvement is common and lungs are commonly involved. Although cardiac disease is responsible for most RA-related deaths, pulmonary disease is also a major contributor, accounting for approximately 10% to 20% of all mortality. Pulmonary disease is a common (60% to 80% of patients with RA) extra-articular complication of rheumatoid arthritis. Its optimal screening, diagnostic, and treatment strategies remain uncertain and are the focus of ongoing investigation. Clinicians should regularly assess patients with rheumatoid arthritis for signs and symptoms of pulmonary disease and, reciprocally, consider rheumatoid arthritis and other connective tissue diseases when evaluating a patient with pulmonary disease of unknown etiology. RA directly affects all anatomic compartments of the thorax, including the lung parenchyma, large and small airways, pleura, and less commonly vessels. In addition, pulmonary infection and drug-induced lung disease associated with immunosuppressive agents used for the treatment of RA can occur.